Determinants of Electronic Health Record Management Independence: A Study of Digital Competence and Admin-istrative Roles in Indonesian Hospitals - Biendha Ulfatullaily; Pipit Festi Wiliyanarti; Yudied Agung Mirasa (International Journal of Public Health, 2026)
The mandatory adoption of Electronic Medical Records (EMRs) in Indonesian hospitals by December 31, 2023, has accelerated digital transformation in healthcare. However, the effectiveness of EMR implementation depends significantly on two critical factors: healthcare professionals' digital competence and the strength of administrative governance structures. This study aims to analyze the influence of digital competence and administrative roles on the independence of electronic health record management in hospital settings. This research employs a quantitative approach with a cross-sectional design at Muhammadiyah Hospital Gresik. Data were collected through structured questionnaires from 66 healthcare professionals, medical record personnel, and administrative staff involved in EMR management. Multiple linear regression analysis was conducted using SPSS to examine partial and simultaneous effects. Digital competence significantly influences EMR management independence (β = 0.606, p < 0.001), while administrative roles also demonstrate significant positive effects (β = 0.351, p < 0.001). Simultaneously, both variables explain 92.7% of the variance in EMR management independence (R² = 0.927). Digital competence and administrative roles are essential determinants of independent EMR management in hospitals. Strengthening both human resource capabilities and administrative governance frameworks is crucial for achieving sustainable health information management in the Indonesian healthcare context.